Effects of 3 days training with hyperoxia on metabolism and systemic circulation - Wang, Y. C.; Smith, R. S.; Jang, J. T. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Mankind`s dreams of running faster on the track have lead sports scientists and coaches to work together to refine the athletes peaking cycle. In this study we looked at the 400m run which is a combination of speed and endurance. Therefore, the aim of this study was to design a training protocol consisted of 3 days training with hyperoxia on the treadmill. The goal was to enhance the athlete`s performance by altering the metabolism and systemic circulation. Methods Training consisted of 3 days training on the treadmill under hyperoxic conditions. Six 400m male track specialist. The research test consisted of a 400m performance (pre - post test). Training tests were separated into day 1 (Tr-1) and day 3 (Tr-3) and represented the intermittent mode, and day 2 (Tr-2) represented continuous running. Intermittent workload Tr-1 and Tr-3 was set at 90 % of the subject`s best time for (3x3x90 %); continuous running was sustained at 50 % performed on Tr-2. Results Results indicated five of the six subjects significantly increased their 400m speed 0.05-0.15 m/s. Only one subject showed no improvement (-0.19 m/s). In the two interval training sessions` (Tr-1, Tr-3) blood lactate concentration indicated a downward trend post test and in the 6th interval, and NH3 in 6th interval training and in the 3rd min of rest (E3) decreased significantly (p <.05). Free radicals(H2O2) indicated no significant change (p>.05). While looking at heart rate during interval training, Tr-1 and Tr-3 indicated a downward trend. Discussion In this study, lactic acid and NH3 showed a downward trend (Tr-1 vs. Tr-3 & T-1 vs. T-2), under high-intensity exercise with hyperoxia, that PCr (phosphocreatine) have diminished its efficiency (stellingwerff et al., 2006) and relative lower production of blood lactate (Hollmann et al., 2002). In this study H2O2 indicated no significant change which was different from Cooper et al (2002) findings. This could possibly be caused by antioxidants (Muna et al., 2001) and HSP70 (Kinnunen et al., 2005) but in order to better understand this further research would need to be conducted. Heart rate in Tr-3 were lower than Tr-1 but it weren`t significant. In 400m speed performance were not significantly improved. These indicated that further time to adapt is required